Virtual network mapping strategy and competitive analysis based on cost constraint - Jianjun YU; Chunming WU (Dianxin kexue)
The approximation algorithm of single virtual network mapping solution aimed to minimize the mapping cost based on convex quadratic programming relaxation was designed. Then aiming for dynamic arrival construction request of the single virtual network，the mapping scheme was achieved based on physical network resource pricing strategy by shadow price，applying above-mentioned approximation algorithm. And then completed the competitive algorithm design based on virtual network admission control strategy by mapping cost constraint and provided the competitive analysis of this algorithm. Experiment results show that the proposed algorithm increases the effective utilization of physical network resources，hence it can improve the virtual network construction request acceptance ratio and the long-term profit of physical network service provider.